Using Grounded Theory to Analyze Qualitative Observational Data that is Obtained by Video Recording - Colin Griffiths (Grounded Theory Review: An International Journal, 2013)
This paper presents a method for the collection and analysis of qualitative data that is derived by observation and that may be used to generate a grounded theory. Video recordings were made of the verbal and non-verbal interactions of people with severe and complex disabilities and the staff who work with them. Three dyads composed of a student/teacher or carer and a person with a severe or profound intellectual disability were observed in a variety of different activities that took place in a school. Two of these recordings yielded 25 minutes of video, which was transcribed into narrative format. The nature of the qualitative micro data that was captured is described and the fit between such data and classic grounded theory is discussed. The strengths and weaknesses of the use of video as a tool to collect data that is amenable to analysis using grounded theory are considered. The paper concludes by suggesting that using classic grounded theory to analyze qualitative data that is collected using video offers a method that has the potential to uncover and explain patterns of non-verbal interactions that were not previously evident.